(untitled) (Global Journal of Science Frontier Research, 1969)
A spectrophotometric study concerning the interaction between cryptand 222 as ndonor and TCNE as π -acceptor has been performed in di and tri chloromethane solutions at temperatures 5, 10, 15, and 20°c. The results of continuous variation and mole ratio methods indicate the formation of 1:1 complexes in both solvents and at all temperatures. The stability constants and the molar absorption coefficients at different temperatures have been calculated from the computer fitting of absorbance-mole ratio data in MATLAB soft ware. The results indicate that Kf values in CHCl 3 are more than the corresponding amounts in CH 2 Cl 2 . In the case of Є, the reverse trend is observed. The H° and S° values were obtained by Vant Hoff method. The obtained data show that the enthalpy of complex formation in two solvents is favorable. While entropy is favorable in the case of CHCl 3 and unfavorable in the case, of CH 2 Cl 2 . The possible reasons for such observation are discussed. The kinetic results confirm an overall second order reaction which is first order with regard to each reactant. The formation of free ions is rejected by the conductometric measurments.